1996
DOI: 10.1172/jci118677
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the fibrinogen D domain self-association/cross-linking site (gammaXL) and the fibrinogen Dusart abnormality (Aalpha R554C-albumin): clues to thrombophilia in the "Dusart syndrome".

Abstract: Cross-linking of fibrinogen at its COOH-terminal gamma chain cross-linking site occurs in the presence of factor XIIIa due to self-association at a constitutive D domain site ("gammaXL"). We investigated the contribution of COOH-terminal regions of fibrinogen Aalpha chains to the gammaXL site by comparing the gamma chain cross-linking rate of intact fibrinogen (fraction I-2) with that of plasma fraction I-9, plasmic fraction I-9D, and plasmic fragment D1, which lack COOH-terminal Aalpha chain regions comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 42 publications
3
33
0
1
Order By: Relevance
“…In fibrinogen Dusart extensive studies have shown that the point mutation Aa 554Arg → Cys results in abnormal lateral aggregation, causing thinner fibrin fibres with significantly decreased gel porosity and increased clot rigidity (Koopman et al, 1993;Siebenlist et al, 1993;Collet et al, 1993). It has also recently been shown that the mutation in fibrinogen Dusart introduces a tendency for the molecules to pre-assemble (Mosesson et al, 1996), and it has been suggested that this characteristic, together with the changes to clot architecture, are the main factors contributing to the high incidence of embolism found in affected individuals. Interestingly, although both these variants arise from point mutations in the aC domain, they have opposite effects on clot structure, indicating that amino acid residues in this region are critical to the function of the aC domain.…”
mentioning
confidence: 99%
“…In fibrinogen Dusart extensive studies have shown that the point mutation Aa 554Arg → Cys results in abnormal lateral aggregation, causing thinner fibrin fibres with significantly decreased gel porosity and increased clot rigidity (Koopman et al, 1993;Siebenlist et al, 1993;Collet et al, 1993). It has also recently been shown that the mutation in fibrinogen Dusart introduces a tendency for the molecules to pre-assemble (Mosesson et al, 1996), and it has been suggested that this characteristic, together with the changes to clot architecture, are the main factors contributing to the high incidence of embolism found in affected individuals. Interestingly, although both these variants arise from point mutations in the aC domain, they have opposite effects on clot structure, indicating that amino acid residues in this region are critical to the function of the aC domain.…”
mentioning
confidence: 99%
“…In this study, the FGA Arg573Cysmutation showed an abnormal fibrin network with thin fibres and a very dense clot, resulting in greater resistance to fibrinolysis. Several studies have shown reduced plasminogen binding for this fibrinogen variant, impaired tPA-induced fibrinolysis [11,37] and increased XL selfassociation and -chain cross-linking [38]. However, for most other cases of thrombosis-related dysfibrinogenaemia, the molecular anomaly is probably not directly responsible for the vascular event but rather a contributing factor to the overall haemostatic balance.…”
Section: Discussionmentioning
confidence: 93%
“…Five independent families with AR554C-albumin binding have been identified and, strikingly, all propositi have presented with thrombosis [26]. Additionally, in vitro studies with the AR554C fibrinogen have demonstrated that impaired fibrinolysis, thinner and many branched fibers, increased clot stiffness, and an increased cross-linking potential probably explain the thrombosis and embolism seen in the families afflicted [22,[27][28][29][30]. It is interesting that for the BArg14Cys variants, which are the immediate vicinity of BGly15 residue and with a potential albumin binding (demonstrated in the propositus of Ijmuiden [12]; however, no others have been analyzed), severe thrombosis such as deep venous thrombosis, pulmonary embolism, or cerebral infarction has been reported in 6 out of the 8 families [4, [10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%